Carthamus tinctorius L. (Safflower) Flower Extract Attenuates Hepatic Injury and Steatosis in a Rat Model of Type 2 Diabetes Mellitus via Nrf2-Dependent Hypoglycemic, Antioxidant, and Hypolipidemic Effects - Nuha Saad Alshareef; Sahar Abdulaziz AlSedairy; Laila Naif Al-Harbi; Ghedeir M. Alshammari; Mohammed Abdo Yahya (Antioxidants)
This study aimed to examine the hepatic and anti-steatotic protective effects of methanolic extract from Carthamus tinctorius (safflower) flowers (SFFE), using a rat model of type 2 diabetes mellitus (T2DM), and to examine the molecular mechanisms underlying these effects. Adult male Wistar rats were used for this study. First, T2DM was induced in some rats by feeding them a high-fat diet (HFD) for 4 weeks, followed by a single dose of streptozotocin (STZ) (35 mg/kg, i.p.). Experimental groups included the following five groups (n = 8 in each): control, control + SFFE, T2DM, T2DM + SFFE, and T2DM + SFFE + brusatol (an Nrf2 inhibitor, 2 mg/kg, i.p.). SFFE was administered at a concentration of 300 mg/kg, and all experiments concluded after 8 weeks. Treatments with SFFE significantly reduced fasting blood glucose levels, free fatty acids (FFAs), cholesterol, triglycerides, and low-density lipoprotein cholesterol in both the control and T2DM rats, but they failed to reduce fasting insulin levels in these groups. SFFE treatments also improved the liver structure and reduced hepatocyte vacuolization and hepatic levels of triglycerides and cholesterol in T2DM rats, in addition to increasing the hepatic mRNA levels of keap1 and the cytoplasmic levels and nuclear activities of Nrf2 in both the control and T2DM rats. SFFE also stimulated the expression levels of PPARα and CPT-1 but reduced the malondialdehyde (MDA), mRNA levels of SREBP1, fatty acid synthase, and acetyl CoA carboxylase in both the control and T2DM rats; meanwhile, it reduced hepatic mRNA and the nuclear activities of NF-κB and increased levels of glutathione, superoxide dismutase, and heme oxygenase-1 in the livers of both groups of treated rats. Furthermore, SFFE suppressed the levels of caspase-3, Bax, tumor necrosis factor-α, and interleukin-6 in the T2DM rats. Treatment with brusatol prevented all of these effects of SFFE. In conclusion, SFFE suppresses liver damage and hepatic steatosis in T2DM through Nrf2-dependent hypoglycemic, antioxidant, anti-inflammatory, and hypolipidemic effects.